Marketing estratégico para la comercialización de ropa femenina de la marca Hugo Wilson segmento medio típico, ciudad de Guayaquil - Cárdenas García, Roxana Mariana (2019)
The theme "Strategic Marketing for the marketing of women's clothing of the brand" Hugo Wilson ", in the typical middle segment of the city of Guayaquil", contains the specific objectives of analyzing the attributes of greater value that women's clothing has "Hugo Wilson "and that affect the purchase decision of customers, select the appropriate distribution channels for the product to reach the end user, identify the online and offline media used by women's clothing customers to learn about the benefits of the products, determine the differentiating advantages that the main competitor of the feminine clothing sector has that defines the commercial strategy to be implemented. The study was based on the deductive method that goes from the general marketing to the particular strategies, applying a quantitative survey through surveys, whose results allowed to develop product strategies for pre-mom women and young adolescents who use sizes plus Market differentiation strategies were elaborated in the concepts of Porter, establishing superior values of the Hugo Wilson brand in front of the competition in product, price, promotion - advertising, place, personnel that determined the ways to reach the final consumer and turn it into a superior value that generates competitiveness before the competition……….